Landslides in Forests around the World Causes and Mitigation - Wen, Haijia; Li, Weile; Xu, Chong; Daimaru, Hiromu (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint, named "Landslides in Forests around the World: Causes and Mitigation", covers various topics, such as the impact mechanism of tree roots on landslide stability, landslide deformation monitoring, landslide disaster prevention and control engineering technology, the automatic identification of regional landslides, susceptibility and hazard assessment, and a rainfall-induced mass landslide warning.